Proposed Equilibrium Framework for Educational Leaders in the Philippines - Dioneda, Mary Grace; Edna Manaig; Pendon III, Fernando (International Journal on Integrated Education, 2025)
This study titled “Proposed Equilibrium Framework for Educational Leaders in The Philippines” aimed explore the experience and strategies of public school heads in work-life balance- their professional and personal life. This study involved 10 school heads of the public elementary and secondary schools in the division of Cabuyao during the School-Year 2024-2025. This phenomenological-transcendental study used interview guide questions as the prime source of data to explore their practices and strategies of the school heads in balancing their professional and personal life. The statements collected from the participants were checked and analyzed by Qualitative Data Analyst. The study revealed that the school heads have experienced balancing professional duties and personal life which highlight both the positive and negative aspects. Just like the other professions, they have faced challenges which include the stress, health issues, and burnout, as well as the time constraint which result to heavy workload. They have also faced difficulties to maintain their personal well-being, frequently sacrificing their leisure activities and the time to be spent for their families due to the unexpected meetings, urgent concerns as well as strict report deadlines. Despite of these challenges, the school heads have employed various coping strategies such as engaging hobbies, spending precious time with their families, and asking supports and technical assistance from the top management. They also emphasized the significance of being proactive and adaptive to manage their professional demands and sustain their productivity. The school heads have described their experiences and strategies to achieve work-life balance my emphasizing the effective time and task management, which also include the prioritization of tasks, delegation, and to create effective schedule. They even highlighted the significance of setting boundaries and maintain to manage the workload effectively. Additionally, they even fostered the supportive work environment through establishing open communication and collaborative problem-solving among school staffs. To maintain their well-being, the school heads prioritized self-care practices which involves taking breaks and staying positive. There are ten themes emerged from the study such Theme1: Struggles in Maintaining Personal Well-being, Theme 2: Intentional Stress Management Through Strategic, Emotional and Personal Well-Being Practices, Theme 3: Strategic Management Personal Boundaries, and Support System: Key Factors contributing to Work-Life Balance; Theme 4: Collaborative Ecosystem for Care and Support; Theme 5: Organized Workflow as Foundation of Work-Life Balance; Theme 6:. Deliberate Separation of Professional and Personal Spheres; Theme 7: Mindful Response to Disruption through Strategic Emotional and Practical Action; Theme 8: Redefining Leadership through Delegation, Empowerment, and Strategic Balance of Work-Life Sustainability; Theme 9: Modeling and Humanizing Leadership to Promote Work-Life Balance; and Theme 10: Work Beyond the Bell: The Extended Realities of Educational Responsibilities. The school heads have described that their experiences in work-life balance as the leader of the school have unleashed the ups and downs in their profession. They showed-off the realities that being leaders do not guarantee to achieve everything in positive way, and so, there is still a need to propose an output that may help them achieve work-life balance through an equilibrium framework for educational leaders.